2021
DOI: 10.1039/d1fo01505b
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating metal ion-regulated flavour formation mechanism in the aging process of Chinese distilled spirits (Baijiu) by electrochemistry, ICP-MS/OES, and UPLC-Q-Orbitrap-MS/MS

Abstract: Elucidating the organometallic interactions in Baijiu will promote a deeper understanding of the flavour formation mechanism during Baijiu aging. However, the organometallic interactions during aging is difficult to explore because...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In our previous study, the impact of electrochemistry on the overall properties of liquor was confirmed ( Xiong et al, 2020 ; Zheng et al, 2021 ). Therefore, we further examined the influence of the electrochemical treatment on the interconversion relationship between those components and the overall aroma of liquor.…”
Section: Resultsmentioning
confidence: 71%
“…In our previous study, the impact of electrochemistry on the overall properties of liquor was confirmed ( Xiong et al, 2020 ; Zheng et al, 2021 ). Therefore, we further examined the influence of the electrochemical treatment on the interconversion relationship between those components and the overall aroma of liquor.…”
Section: Resultsmentioning
confidence: 71%
“…In addition, literatures reported that flavonoids act as highly active antioxidants by way of metal chelation [ 36 ]. Thus the concentrations of the metals in Baijiu were determined by ICP-MS/OES analysis [ 44 ]. It is found that eight metals (Al, Ba, Ca, Cu, Fe, Mg, K, and Na) have a relatively high content.…”
Section: Resultsmentioning
confidence: 99%
“…The aging of Baijiu is a complicated and dynamic process, and is the result of various physical and chemical reactions. The aging mechanisms generally cover volatilization of irritant components with low boiling point; hydrogen bond association between alcohol and water; oxidation, esterification and hydrolysis among alcohols, aldehydes, acids and esters ( Ma et al, 2019 , Zheng et al, 2021a , Deng et al, 2020 ). In this part, more scientific molecular mechanisms of different traditional aging methods and artificial aging technologies will be clarified clearly based on the present research to promote comprehensive understanding of Baijiu aging process and development of novel artificial aging technology of Baijiu.…”
Section: Molecular Mechanisms Of Baijiu Agingmentioning
confidence: 99%
“…Cyclic and square wave voltammetry confirmed that Baijiu system include both combination and free state of metal ions. During the aging period, the concentration of total metal ions and organic acids showed an upward trend and significant organometallic interactions performed between them ( Zheng et al, 2021a ). The increase of organic acids facilitated the transformation of metal ions from complex to free state ( Fig.…”
Section: Molecular Mechanisms Of Baijiu Agingmentioning
confidence: 99%